Development of Financial Management Applications at Health Clinics Using Extreme Programming Methods - Denny Jean Cross Sihombing (Jurnal Info Sains : Informatika dan Sains, 2023)
In the face of complex financial challenges, such as increasing operational costs, decreasing patient numbers, and fluctuating revenues, health clinics must implement intelligent and efficient financial strategies. This research focuses on developing a financial information system to improve efficiency, transparency, and control in the financial management of the clinic. Steps towards the launch, including feature integration, retrospective evaluation, and phased rollout, were implemented to minimize the impact on clinic operations. Evaluating the impact of the system after launch is an important step to ensure the expected benefits are achieved, and continuous improvement through retrospective sessions is critical to continuously improving the development process. The results of this study provide a comprehensive view of the development strategy of a clinic financial management application using the XP approach, which can serve as a foundation for clinics to deal with the complexities and dynamics of managing their financial aspects. This research contributes to understanding best practices in dealing with financial challenges in the healthcare sector.